The Effect of Horror Film on Mental Conditions in Students of UIN Raden Fatah Palembang - Rahmatullah, Imam Ragil; Azis, Ridyarsa Emir; Reygi Pratiwi; Muhammad Rahman Putra; Kesha Aryka Nurfadillah; Fitria Puspita Sari (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This study examines the effect of horror films on the mental condition of early adulthood (20-22) which is observed in 2 domains, namely the level of anxiety and emotional control. chi square method or chi square. The results showed that 19 samples with a high frequency of watching horror films experienced a high level of anxiety, they easily felt anxiety, while 11 samples with a low frequency of watching horror films showed a low level of anxiety, but the emotional control of horror films did not affect the realm of emotional control.